Biochar with or without pig manure affects chemical properties of soil and maize yield - Akande, Tolulope Yetunde; Xiaoqing, Li; Adegoke, Toluwase Oreoluwa; Taipeng, Sun; Wang, Hongyan (Journal of Degraded and Mining Lands Management, 2024)
In many parts of the globe, agricultural soil degradation and nutrient loss both contribute to the decline of soil quality. The utilization of various organic sources has provided meaningful trends in sustainable agriculture. The research was carried out to examine how biochar (B) and pig manure (PM) affected soil chemical properties as well as the growth and yield of maize for two years. A randomized complete block design was adopted with three replications. The soil was amended with biochar and pig manure at two rates (15 and 30 t ha-1): biochar (B15 and B30), pig manure (PM15 and PM30), biochar with pig manure (BPM15 and BPM30), respectively, and control (CK). The incorporation of biochar and pig manure together at 15 and 30 t ha-1 improved soil organic carbon (SOC), total nitrogen (TN) and available phosphorus (AP) compared to control. Individual use of pig manure at 15 and 30 t ha-1 significantly decreased compared to its combination in SOC, TN and AP. The combined use of biochar and pig manure at 15 t ha-1 significantly increased compared to the lone addition of biochar in SOC, TN and AP. The application of organic amendments significantly increased plant height, dry matter yield, and grain yield in both years. The relationship pattern was measured between soil properties and agronomic characteristics. The use of biochar and pig manure separately or together offers strong potential to improve soil fertility and increase crop productivity in soils.